SEBARAN KOMODITAS TERNAK UNGGULAN DI JAWA DAN LUAR JAWA IMPLIKASINYA BAGI PERDAGANGAN TERNAK - HENDAYANA, RACHMAT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005)
The superior livestock commodity owns strategic position to be developed in region base on technical (land and climate conditions), socio economics, and institutions consideration. This research aim to discuss superior livestock commodity in Java and off Java and also the implication for livestock trading. Discussion conducted base on secondary data provided by CBS (Central Bureau of Statistics) for five year period (1997 - 2001). Location Quotient ( LQ) approach uses for data analysis and result shows: ( a) The performance of livestock population for ruminant and non ruminant in every province either in Java and Off Java shows variative, ( b) With LQ approach known that region of province have potential selected superior livestock type to be commercialized. In this case province owning superior livestock shown by value of LQ which was high relative (> 1), (c) Potential gap of livestock population in every province push the happening of interisland livestock trading either in Java and Off Java.
Keywords: Superior Livestock, Location Quotient, Trade, Java, Off Java